5-year results of the 1.5 cm incision Achilles tendon repair. (December 2017) - Ling, Samuel K.K.; Slocum, Amanda; Lui, T.H.
Highlights: The 1.5 cm Achilles repair is a cost effective procedure which does not require specialised instruments. It does not require intensive rehabilitation resources. Functional outcome of the 1.5 cm Achilles repair is good and is sustained for over 5 years. It enables application of a strong locking suture while maintaining minimal nerve and wound complications Abstract: Background: To study a hypothesis that the cost-effective 1.5 cm medial incision Achilles tendon repair technique will provide good functional outcomes which are maintained for over 5 years. Method: Prospective study of 12 consecutive cases with a minimal 5-year follow-up were recruited from April 2008 to November 2010. Cases whom were mentally incompetent or those which required concomitant procedures were excluded. Outcomes measures included the numeric pain rating scale, motor power strength, range of motion, functional scoring using the AOFAS hindfoot score and patient's self-assessment using the Foot and Ankle Outcome Score (FAOS). Result: No re-ruptures or sural nerve injured were identified after a minimal 5-year follow-up. Pain was minimal at 0.5/10, calf power was 5/5 and ankle range was good (plantarflexion: 38°/dorsiflexion: 21°). The AOFAS hindfoot score was 97.4 and all 5 sub-categories of the Foot and Ankle Outcome Score (FAOS) were good. Conclusion: The 1.5 cm medial incision repair of the Achilles tendon is an economically sound surgical technique, with minimal complications, which gives good medium length functional outcomes. Level of evidence: IV.